Radionanomedicine Combined Nuclear and Nanomedicine (Biological and Medical Physics, Biomedical Engineering, 2018)
This book describes radionanomedicine as an integrated medicine using exogenous and endogenous This book describes radionanomedicine as an integrated approach that uses exogenous and endogenous nanomaterials for in vivo and human applications. It comprehensively explains radionanomedicine comprising nuclear and nanomedicine, demonstrating that it is more than radionanodrugs and that radionanomedicine also takes advantage of nuclear medicine using trace technology, in which miniscule amounts of materials and tracer kinetic elucidate in vivo biodistribution. It also discusses exogenous nanomaterials such as inorganic silica, iron oxide, upconversion nanoparticles and quantum dots or organic liposomes labelled with radioisotopes, and radionanomaterials used for targeted delivery and imaging for theranostic purposes. Further, it examines endogenous nanomaterials i.e. extracellular vesicles labelled with radioisotopes, known as radiolabelled extracellular vesicles, as well as positron emission tomography (PET) and single photon emission computed tomography (SPECT), which elucidate the biodistribution and potential for therapeutic success.